KONSELING EKSISTENSIAL HUMANISTIK MENGGUNAKAN MEDIA KOMIK DIGITAL DALAM MENINGKATKAN KEBERMAKNAAN HIDUP ANAK PANTI ASUHAN AL-FATIH - Shadyah, Nurul; Suryati, Suryati; Janare Putra, Bela (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2023)
The aim of this research is to first find out the meaning of children's lives before being given humanistic existential counseling using digital comic media. Second, the meaningfulness of children's lives after being given humanistic existential counseling using digital comic media. And third, to find out whether humanistic existential counseling using digital comic media is effective in increasing the meaningfulness of life for children at the Al-Fatih orphanage. This research method uses a quantitative approach with experimental research type and one group pretest and posttest design. From a total population of 30 children, 10 samples were taken. The data collection technique in this research used documentation and a questionnaire with a total of 19 statements which had been tested for the validity of rcount > rtable with a value range of rcount 0.391-0.639 and rtable 0.390. Data analysis techniques use normality tests and hypothesis testing. The results of the research show that the majority of children in the Al-Fatih orphanage are in the medium category. From the results of the normality test, the pretest was 0.191 and the posttest was 0.457 and the T test showed that the significant value (2-tailed) of 0.000 was smaller than 0.05, meaning that Ha was accepted and H0 was rejected, and there was a difference between the pretest and posttest. Therefore, humanist existential counseling using digital comic media has an influence in increasing the meaningfulness of the lives of Al-Fatih orphanage children